Pengaruh kombinasi tepung terigu dan jamur tiram (Pleurotus ostreatus) terhadap sifat organoleptik nugget - Yuniartini, Ni Luh Putu Sherly; Nugrahani, Rizki (Journal of Agritechnology and Food Processing, 2022)
A nugget is a processed product of ground beef which is added to a binder and mixed with spices and then covered with egg white (batter) and breaded flour (breading), which is then packaged before being fried and frozen to maintain quality. Many raw materials were used in its development, including oyster mushrooms (Pleurotus ostreatus). Oyster mushrooms contain high fiber in contrast to chicken or beef, which have low fiber, and oyster mushrooms also have a texture and taste similar to chicken meat. High fat content and low fiber in chicken or beef are not recommended for people who are obese or hypercholesterolemic, so oyster mushrooms are a good choice as an ingredient for making nuggets. The combination of wheat flour and oyster mushroom has an effect on the organoleptic properties of the taste, aroma, and texture of the nuggets. The making of nuggets with a combination of wheat flour and oyster mushrooms was acceptable organically, and the panelists gave the impression of liking it for all organoleptic criteria. The average result of the best organoleptic test assessment in this study was the N5 treatment, namely 60% wheat flour and 40% oyster mushroom with organoleptic characteristics of taste, aroma and texture favored by the panelists.